POTENSI BIJI BESI DI DAERAH AMBULANGAN, BANJAR, KALIMANTAN SELATAN - Sunarie, Cecep Yandri (Fakultas Teknik Geologi Universitas Padjadjaran, 2008)
Research area is located in Ambulangan, Banjar regency of South Kalimantan province. The research is aimed to indentified and mineral inventory of Iron Ore deposit, as well as primary or secondary type ore deposit. Morphology of the area is generally covered by hilly volcanic terrain with elevation below 650 m above sea level, the drainage pattern is mainly sub-parallel.Litology of the study area is covered mainly by Cretaceous rocks consists of Sediment, volcanic and andesitic intrusion.The iron ore occurred as primary and secondary type deposit. The primary type is exposing as vein like structure of approximately 6 m width and 50 m long, where as the secondary type is exhibiting as boulder or lateritic soil. Chemical analysis of primary iron ore indicated the ore grade is about 66.37% and 62.99% for secondary iron ore.